(untitled) (Bangladesh Journal of Botany, 2015)
Phosphorus deficiency in lentil (Lens culinaris Medik.) resulted in the development of abundant long root hairs which were rudimentary in plants fed with phosphorus. Root and stem diameter as well as thickness of leaf reduced under phosphorus deficiency. The cortical zone of the stem and root was found to decrease under phosphorus deficiency. Vascular area became smaller with less number of xylem vessels and smaller size of the cavity due to phosphorus deficiency. The pith area was increased in the stem under phosphorus deficient condition. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22726 Bangladesh J. Bot. 44(1): 73-78, 2015 (March)